Primary biliary cholangitis in Spain. Results of a Delphi study of epidemiology, diagnosis, follow-up and treatment - Parés, Albert; Albillos, Agustín; Andrade, Raul Jesús; Berenguer, Marina; Crespo, Javier; Romero-Gómez, Manuel; Vergara, Merc; Vendrell, Belén; Gil, Alicia (Revista española de enfermedades digestivas, 2018)
primary biliary cholangitis (PBC) is a rare disease with limited data regarding its epidemiology and standard clinical management in Spain. to gain insight into the epidemiology, patient flow, diagnosis, follow-up and treatment of PBC in Spain. a review of the literature and Delphi study involving 28 specialists in two rounds of consultations and an in-person results validation workshop. there are approximately 9,400 patients with PBC in Spain, with an annual incidence of 0.51-3.86 cases/100,000 population. Albeit, a high error margin may be presumed due to the scarcity of relevant studies on this subject. Several months may elapse from suspicion to a confirmed diagnosis, usually by a gastroenterologist or hepatologist. The role of the liver biopsy for diagnosis and follow-up is heterogeneous. Overall, 95% of patients are treated with ursodeoxycholic acid (UDCA) and response is primarily monitored using the Barcelona criteria. Follow-up is performed every six months, with a heterogeneous use of the various available techniques. No recommendations or second-line commercial drugs are available in the case of no response, inadequate response or intolerance to UDCA. while epidemiology may be estimated based on expert opinions, national registries are needed to provide accurate, up-to-date information on epidemiological parameters, disease stage and response to treatment in patients with PBC. Furthermore, novel therapies are required for selected patient groups.